CAUSES AND CONSEQUENCES OF MASS MIGRATION OF KAZAKHS TO CHINA IN 20-30 YEARS - Омарканова Асель Омаркановна; Красикова Анастасия Максимовна; Пифан Анастасия Витальевна (European Research Materials, 2025)
This article examines the main prerequisites and reasons for the mass migration of Kazakhs to China, measures to counter the migration, and consequences. Much attention in the article is paid to the territorial issue